Internet resource and usage - Atanda, Balogun Naeem; Ahlan, Abdul Rahman; Oluwatosin, Sulyman-Haroon Shakirat (Ilorin Press, 2019)
Individuals and organisations in all sectors of human activity, including in business, education, banking, and the public sector are increasingly dependent on new technologies to perform their activities and enhance their communication and interrelationships toward achieving their various goals. These goals may be personal development, greater effectiveness and efficiencies, better products or services, or higher profits. At the same time there are growing concerns regarding the dangers of underuse, overuse or misuse of these technologies in the digital era. Therefore, in order to be able to use the new technologies to create desirable values for themselves and society, people need to adequately understand, and appropriately use and adapt the benefits the technologies offer, and also understand and protect themselves from the associated dangers.